Serious Human Rights Violations (The Role of the National Commission on Human Rights, the Human Rights Prosecutor's Office, and the Human Rights Court) - Dinda Suciana Rambe; Yolanda Ayu Gita; Tasya Devina Putri Harahap; Putri Nabila Aryhati Solin (ISNU Sumatera Utara, 2025)
Gross violations of human rights are serious crimes that require a specific and integrated legal mechanism. In Indonesia, their handling involves several key institutions, namely the National Commission on Human Rights (Komnas HAM), the Attorney General's Office through its division of prosecution of gross human rights violations, and the Human Rights Court. This study aims to analyze the role and authority of each institution in the process of enforcing the law against gross human rights violations, while also assessing the effectiveness of coordination between these institutions. The research method used is normative legal research with a statutory and conceptual approach, through a review of Law Number 26 of 2000 concerning the Human Rights Court and related regulations. The results of the study indicate that although the authority of each institution has been clearly regulated, in practice, various obstacles remain, such as differences in interpretation of authority, weak coordination, and political and administrative obstacles. Therefore, strengthening the legal framework and inter-institutional coordination mechanisms is necessary to achieve effective human rights law enforcement and justice.